Social Learning Theory Dan Perilaku Agresif Anak Dalam Keluarga - Qurrotul Ainiyah (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2017)
Abstract This research is study of library research that raised Social Learning Theory applied in family, in order to be able to form socially sensitive individuals toward Indonesian peace. In this paper there are three questions: First, what are the basic concepts in Social Learning Theory? Second, how is the application of social learning theory in the family context? Third, how is the application of Social Learning Theory in the family able to create peace in Indonesia? So the result of this research is: First, Social learning theory is the theory of learning and the formation of personality behaviorally, and emphasized the importance of the social environment. Such individuals, in this theory, are regarded to have self-efficacy that makes socially competent. Second, in the family system, social learning theory is applied to form the quality of individuals who have self efficacy that can't be seen as a mere personal effort. But as part of a social institution that can only be achieved by working together through an interconnected effort. Third, Social learning theory can form individual personality in response to social stimulus, which will impact on the good formation character of the nation's generation that is sensitive to social.   Abstrak Penelitian ini adalah kajian library research yang mengangkat Social Learning Theory diterapkan dalam keluarga, agar mampu membentuk individu yang peka terhadap social menuju perdamian Indonesia. Dan dalam paper ini terdapat tiga pertanyaan: Pertama,apa saja konsep-konsep dasar dalam Social Learning Theory. Kedua, Bagaimana penerapan social learning theory ini dalam konteks keluarga?. Ketiga, bagaimana penerapan Social learning Theory dalam keluarga mampu menciptakan perdamaian di Indonesia?.Maka hasil dari penelitian ini adalah Pertama, Social learning theory adalah teori tentang pembelajaran dan pembentukan kepribadian secara behavioral.Ia menekankan pentingnya lingkungan social. Individu yang demikian, dalam teori ini, dipandang memiliki efikasi diri (self-efficacy) yang membuatnya cakap secara sosial. Kedua, Dalam sistem keluarga, social learning theory diterapkan membentuk kualitas individu yang memiliki efikasi diri yang tidak mungkin dilihat sebagai upaya personal belaka. Tapi Sebagai bagian dari sebuah lembaga social yang hanya bisa dicapai dengan bekerja sama melalui usaha yang saling berhubungan. Ketiga, Social learning theory dapat membentuk kepribadian individu sebagai respons atas stimulus sosial, yang akan berimbas pada bagusnya pembetukan karakter generasi bangsa yang peka terhadap social.